2011
DOI: 10.1055/s-0031-1284434
|View full text |Cite
|
Sign up to set email alerts
|

Liver Abnormalities in Cardiac Diseases and Heart Failure

Abstract: Heart failure (HF) is characterized by the inability of systemic perfusion to meet the body's metabolic demands and is usually caused by cardiac pump dysfunction and may occasionally present with symptoms of a noncardiac disorder such as hepatic dysfunction. The primary pathophysiology involved in hepatic dysfunction from HF is either passive congestion from increased filling pressures or low cardiac output and the consequences of impaired perfusion. Passive hepatic congestion due to increased central venous p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
159
1
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(179 citation statements)
references
References 31 publications
(35 reference statements)
10
159
1
9
Order By: Relevance
“…In cardiac hepatopathy, the primary pathophysiology is either passive venous congestion that results in "congestive hepatopathy (CH)" or low cardiac output and arterial hypoperfusion that results in "acute cardiogenic liver injury (ACLI)" (14,15,17,18). In literature, ischemic hepatitis, shock liver, or hypoxic hepatopathy have also been used instead of ACLI, however, we propose that ACLI provides more details about the underlying pathophysiological process (18,19).…”
Section: Pathophysiology Of Liver Damagementioning
confidence: 99%
See 3 more Smart Citations
“…In cardiac hepatopathy, the primary pathophysiology is either passive venous congestion that results in "congestive hepatopathy (CH)" or low cardiac output and arterial hypoperfusion that results in "acute cardiogenic liver injury (ACLI)" (14,15,17,18). In literature, ischemic hepatitis, shock liver, or hypoxic hepatopathy have also been used instead of ACLI, however, we propose that ACLI provides more details about the underlying pathophysiological process (18,19).…”
Section: Pathophysiology Of Liver Damagementioning
confidence: 99%
“…CH generally occurs in the setting of chronic cardiac conditions that may increase systemic venous pressure such as chronic HF, constrictive pericarditis, mitral stenosis, tricuspid regurgitation, cor pulmonale, severe pulmonary arterial hypertension, long-standing Fontan procedure, or right-sided HF of any cause. Acute cardiogenic liver injury, however, is most commonly associated with acute cardiocirculatory failure resulting from acute myocardial infarction, acute decompensated HF (ADHF), myocarditis, or massive pulmonary embolism (17,18). In fact, passive congestion secondary to right-sided HF and reduced arterial perfusion and oxygenation due to left-sided HF often coexist and potentiate the deleterious effects of each other on the liver (11,14,19,20).…”
Section: Pathophysiology Of Liver Damagementioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we tested the hypothesis in HF patients admitted to the Cardiovascular Disease Department of Niigata University Medical and Dental Hospital. In addition, pulmonary arterial hypertension (PAH) generally leads to right HF and sometimes cause to LC (Alvarez and Mukherjee 2011). It has been reported that inappropriately raised hepcidin levels may be a causative factor for FID of patients with PAH (Rhodes et al 2011), but the mechanisms of increased hepcidin levels in PAH are largely unknown.…”
Section: Introductionmentioning
confidence: 99%